Damage of reinforced concrete beams consisting modified artificial polyethylene aggregate (MAPEA) under low impact load - Mokhatar, Shahrul Niza; Mohd Zuki, Sharifah Salwa; Hadipramana, Josef; Kamarudin, Ahmad Fahmy; Md Noh, Mohammad Soffi; Mustafa, Mohamed Muftah; Norshahimi, Nurul Shazlin (Construction Research Institute of Malaysia (CREAM), 2018)
The impact damage of reinforced concrete beams subjected to low velocity impact loading at the ultimate load range are explored. In this study, an impact tests is carried out on reinforced concrete beam consisting Modified Artificial Polyethylene Aggregate (MAPEA), where, an approximately 100 kg of impact weight were dropped three times onto the beam specimens until its fails. The waste plastic bags, that encapsulated by glass powder as known as MAPEA were used as the replacement of coarse aggregate. There are twelve beam specimens of size 120 mm x 150 mm x 800 mm are categorized into three groups, where each group consists of 4 specimens. The three groups denoted as normal reinforced concrete (NRC), reinforced concrete with MAPEA concrete block infill (RCAI) and reinforced concrete with 9% of MAPEA as a coarse aggregate (RC9A). All specimens were tested under low velocity impact loads under 0.32 m and 1.54 m (2.5 m/s & 5.5 m/s velocities) drop height of impact weight. The comparisons were made between the three types of beams under the aspect of failure (shear and flexural) and its final displacement. The result of the laboratory test showed that the RC9A beams produced less crack and low value of residual displacement.